Изучение структуры популяций растений на отвалах угольных шахт Донбасса - Сетт, И.В. (Промышленная ботаника, 2004)
The results of studying age and vitalistic structures and populations density of perennial plant species on coal mine dumps of Donbass are presented in the article. The species studied are as follows: Achillea pannonica Scheele, Festuca rupicola L.,Oxytropis pilosa (L.) DC., Agropyron pectinatum (Bieb.) Beauv.) and Stipa ucrainica P. Smirn. Incompleteness of age spectra of some populations can be connected with unfavorable ecologic conditions on mine dumps.